Researchers’ Ethical Concerns About Using Adaptive Deep Brain Stimulation for Enhancement - Kostick-Quenet, Kristin; Kalwani, Lavina; Koenig, Barbara; Torgerson, Laura; Sanchez, Clarissa; Munoz, Katrina; Hsu, Rebecca L.; Sierra-Mercado, Demetrio; Robinson, Jill Oliver; Outram, Simon; Pereira, Stacey; McGuire, Amy; et al. (Frontiers in Human Neuroscience, 2022)
The capacity of next-generation closed-loop or adaptive deep brain stimulation devices (aDBS) to read (measure neural activity) and write (stimulate brain regions or circuits) shows great potential to effectively manage movement, seizure, and psychiatric disorders, and also raises the possibility of using aDBS to electively (non-therapeutically) modulate mood, cognition, and prosociality. What separates aDBS from most neurotechnologies (e.g. transcranial stimulation) currently used for enhancement is that aDBS remains an invasive, surgically-implanted technology with a risk-benefit ratio significantly different when applied to diseased versus non-diseased individuals. Despite a large discourse about the ethics of enhancement, no empirical studies yet examine perspectives on enhancement from within the aDBS research community. We interviewed 23 aDBS researchers about their attitudes toward expanding aDBS use for enhancement. A thematic content analysis revealed that researchers share ethical concerns related to 1) safety and security; 2) enhancement as unnecessary, unnatural or aberrant; and 3) fairness, equality and distributive justice. Most (70%) researchers felt that enhancement applications for DBS will eventually be technically feasible and that attempts to develop such applications for DBS are already happening (particularly for military purposes). However, researchers unanimously (100%) felt that DBS ideally should not be considered for enhancement until researchers better understand brain target localization and functioning. While many researchers acknowledged controversies highlighted by scholars and ethicists, such as potential impacts on personhood, authenticity, autonomy and privacy, their ethical concerns reflect considerations of both gravity and perceived near-term likelihood.